PENGARUH CITRA MERK DAN HARGA TERHADAP LOYALITAS KONSUMEN PRODUK AIR MINERAL (STUDI KASUS PADA PELANGGAN MAHASISWA AKADEMI MANAJEMEN ADMINISTRASI YOGYAKARTA) - Cinthia Mutiara Hapsari; Subiyantoro, Ary (Kajian Ekonomi dan Bisnis, 2025)
This research aims to determine how the influence of brand image and price on consumer loyalty in a case study of students of the Yogyakarta Administrative Management Academy. Data analysis techniques use validity tests, reliability tests, multiple regression analysis, f tests and t tests. Based on the results of the study, the multiple regression equation Y = 3.072 + 0.421X1 + 0.516X2 was obtained, indicating that there is an influence between brand image and loyalty on consumer satisfaction. From the results of the determination coefficient test, it shows that R Square is 0.661. This means that the magnitude of the influence of brand image and loyalty variables on consumer loyalty in a case study of students of the Yogyakarta Administrative Management Academy is 66.1%, while the remaining 33.9% must be explained by other causal factors that come from outside this regression method.